STUDY OF FINE PECULIARITIES OF HEAT CAPACITY IN YBa$_2$Cu$_3$O$_y$ FILMS BY MEANS OF THE LASER-COUPLED FLAT-COIL-OSCILLATOR - Gevorgyan, S.G.; Karapetyan, G.H.; Shirinyan, H.G.; Muradyan, S.T.; Gevorgyan, G.S.; Kurghinyan, B.K.; Gevorgyan, V.S.; Polyanskii, A.A. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2011)
Improvements in the “hybrid” imaging method, based on traditional Laser Scanning Microscopy in combination with the single-layer flat-coil-oscillator (SFCO) sensitive technique introduced by authors earlier, are discussed. This method is capable of imaging 2D-grained structure, as well as the normal-to-superconductive phase transition in flat thin high-Tc superconductive materials with 1–2 μm spatial resolution. It enabled to detect weakly expressed peculiarities of the heat capacity in YBa2Cu3Oy film (preceding the well-known specific heat “jump”), which are important for true understanding of the real nature of superconductivity phenomenon. The method uses a well-focused He-Ne laser beam as a probing signal, and the SFCO-technique as a high-resolution sensing tool.
Keywords: Cryogenic laser scanning microscope (CLSM); imaging technique; heat capacity of YBa$_2$Cu$_3$O$_y$ film; high-$T_c$ superconductive (HTS) & low-$T_c$ superconductive (LTS) materials; normal-to-superconductive (N/S) phase transition; single-layer flat-coil-oscillator test-method (SFCO-technique)